“that damned old business of the war in the members”: The Discourse of (In)Temperance in Robert Louis Stevenson’s The Strange Case of Dr Jekyll and Mr Hyde - Butler, Lisa (Romanticism on the Net, 2006)
AbstractRobert Louis Stevenson’s 1886 novella, The Strange Case of Dr. Jekyll and Mr. Hyde, has historically been read as a “timeless” allegory dramatizing the fundamental conflict between the “good” and “evil” elements of human nature. More recent readings of the novel, however, have put forth historicized interpretations of the text emphasizing its engagements with the cultural developments of late-nineteenth-century Britain. This article builds upon these historicized readings, arguing that Stevenson’s novella is reflective of the anxieties engendered by current theories of evolutionary degeneration and, more specifically, its manifestations in illicit behaviour, especially in the areas of alcohol consumption and sexual expression. Stevenson’s novel actively critiques those cultural sites most vocal in articulating such anxieties, namely the temperance and social purity movements of the later nineteenth century. Dr. Jekyll and Mr. Hyde thus deploys a language of (in)temperance to interrogate the potentially destructive results of an evolutionary model which posits the subject as already split between his or her civilized (moral) and barbaric (immoral) selves.